Optimalisasi Digital Marketing pada Komunitas Klinik Usaha Desa Kucur untuk Kemajuan Ekonomi Desa Kucur - Basory, Hartomy Akbar; Hellyani, Catharina Aprilia; Cahyadi, Rino Tam; Wahyono, Seno Aji; Manalu, Sahala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The influence of attraction and social media presents several problems and benefits that will be discussed in this study. Social media is considered as one of the best ways for entrepreneurs to promote their products to attract potential customers. The increasing number of social media users makes entrepreneurs use social media influencers as one of the supporting elements in marketing their products. This study aims to analyze the effect of social network appeal on the sales level of Hanania Milk Pie products. This research methodology uses document reviews, interviews, and Instagram social media data insights that can be taken into consideration by food industry entrepreneurs. This research results in that food souvenir products can optimize digital marketing to achieve promotion in several major cities within the country and outside with promotional costs that are much cheaper than promotional models using print media or electronic media so as to increase public trust and increase purchases. The current trend for millennials is entering globalization, changes in consumer behavior, mobility, and accessibility of information. The growth of digitalization has impacted both the consumer and producer sides of the transaction market. One of them is the ability to now buy, sell, market, order, and pay for products online. This research applies the literature study method. In this journal, a series of interrelated activities are carried out by collecting library data, reading, storing data, and managing data materials for research. Based on the results and discussion, it can be said that, in the face of rivalry in business development, business actors, both micro, small and medium enterprises, MSMEs, must take into account digital marketing as one of the strategies. To support this, the majority of MSMEs agreed on three metrics for digital marketing, namely: providing clear information to consumers, assisting MSMEs in expanding market reach, and making it easier to communicate with consumers to better fulfill customer demands.